Khảo sát cơ chế ức chế ăn mòn của một số amit của axit béo tổng hợp n-parafin dầu mỏ Việt Nam. - Kha, Đinh Văn; Thụ, Lục Văn; Quế, Lê Xuân (Vietnam Journal of Chemistry, 2012)
Aliphatic acids oxidatively synthesized from Vietnam petrol n-paraffin were used for preparation of 4 amides RCONH2 (A4), RCONH–CH2–CH2OH (A5), RCON(CH2–CH2OH)2 (6b), and RCONH–(CH2)2–NH–COR (7c). A corrosion inhibition ability of the amides has been examined using electrochemical method. 3wt% NaCl solution has been used as a background electrolyte in which the amides were dissolved as a corrosion inhibitor at concentration 1wt%. Corrosion potential Ecor, corrosion current icor and some others corrosion parameters measurements have been performed in the electrolytes at room temperature. It is found that derivatives A5 and A4 show better inhibition ability than the remaining substances. The difference of the inhibition ability was attributed to the calculated adsorption coeficient kads of the amides. The mechanism of corrosion inhibition of some synthesized amides has been discussed.